Identidad, reconocimiento y participación. Ordenamiento territorial y justicia ambiental en las zonas rurales de Medellín (Colombia) (2015)
ABSTRACT: This article presents the results of an investigation where environmental justice and communication for social change are used for social change as theoretical concepts. It develops with participatory methodologies in the context of rural areas of Medellin in 2013. Their goal is to identify and classify the perceptions of the social actors involved in the policies. The results found are (i) a wide range of social actors, (ii) a high level of dispersion of actions in all rural territories and (iii) a few local identities in constant change and reconstruction, but always associated with rural life. The article concludes by highlighting some collective perceptions in response to environmental effects of the model of urban expansion and how social actors in five rural areas of the municipality of Medellín have a legacy of community participation processes with the potentiality to influence local actions in a environmental justice.